Estudo da relação entre a composição química, energia de falha de empilhamento e transformação de fases na zona fundida em soldagem com arame tubular à base de Fe-Mn-Ni e avaliação da ZAC em um tubo centrifugado de liga Fe-27Mn-1Si - Ribamar, Giovani Gonçalves (2018)
Steels with high manganese content have been gaining more prominence due to their high toughness in cryogenic environments and excellent allied resistance and high ductility. These materials have a structure composed of austenitic matrix, and may present ferrite, α’ martensite and ε martensite, depending on the content of the alloying elements. The properties of these materials are often related to the mechanism of austenite deformation, either for the formation of martensite or for the formation of twins during deformation. This deformation mechanism is often related to the stacking fault energy that the material possesses. Studies show that SFE values between 0 and 8 mJ/m2 provide formation of ε martensite during deformation, whereas only twins are formed for energies above 18 mJ/m2. Intermediate values provide the formation of both ε martensite and twins. In this way it is possible to predict the microstructure and, consequently, mechanical properties with the SFE knowledge of the material. However, there is a problem when welding of these materials is concerned, since most of the current studies on their weldability are restricted to welding of the autogenous type, such as laser welding and electric resistance welding, due to the shortage of welding consumables for these materials. In this work a study of the effect of the chemical composition of the molten zone was carried out, by means of the change of the dilution, using a consumable with high manganese content in SAE 1012 carbon steel plate with the flux-cored arc welding; an algorithm was developed for the calculation of SFE by the thermodynamic method; the microstructures to verify the prediction made with the energy of stacking fault were obtained by optical microscopy and scanning electron microscopy. The deposition of the electrode on the SAE 1012 steel surface generated different chemical compositions in the weld metal that varied as a function of the dilution. Conditions with dilution values between 7 and 41% were produced. Low dilution conditions presented positive SFE, while its microstructure showed only austenite. For the high dilution conditions, the chemical composition of the molten zone presented negative SFE, and its microstructure was composed of austenite and ε martensite.